Contested territory : Điện Biên Phu̓ and the making of northwest Vietnam - Lentz, Christian C. (Yale agrarian studies., 2019)
The definitive account of one of the most important battles of the twentieth century, and the Black River borderlands' transformation into Northwest Vietnam This new work of historical and political geography ventures beyond the conventional framing of the Battle of Điện Biên Phủ, the 1954 conflict that toppled the French empire in Indochina. Tracking a longer period of anticolonial revolution and nation-state formation from 1945 to 1960, Christian Lentz argues that a Vietnamese elite constructed territory as a strategic form of rule. Engaging newly available archival sources, Lentz offers a novel conception of territory as a contingent outcome of spatial contests.